Mitochondrial genomes of the jungle crow Corvus macrorhynchos (Passeriformes: Corvidae) from shed feathers and a phylogenetic analysis of genus Corvus using mitochondrial protein-coding genes. (3rd July 2016) - Krzeminska, Urszula; Wilson, Robyn; Rahman, Sadequr; Song, Beng Kah; Seneviratne, Sampath; Gan, Han Ming; Austin, Christopher M.
Abstract: The complete mitochondrial genomes of two jungle crows ( Corvus macrorhynchos ) were sequenced. DNA was extracted from tissue samples obtained from shed feathers collected in the field in Sri Lanka and sequenced using the Illumina MiSeq Personal Sequencer. Jungle crow mitogenomes have a structural organization typical of the genus Corvus and are 16, 927 bp and 17, 066 bp in length, both comprising 13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal subunit genes, and a non-coding control region. In addition, we complement already available house crow ( Corvus spelendens ) mitogenome resources by sequencing an individual from Singapore. A phylogenetic tree constructed from Corvidae family mitogenome sequences available on GenBank is presented. We confirm the monophyly of the genus Corvus and propose to use complete mitogenome resources for further intra- and interspecies genetic studies.